Respuesta :

Answer: 5x + 7n + 4    

Step-by-step explanation:

(7x + 7n) + (-2 - 2x) + (6n + 6)        ---> original problem

7x + 7n -2 - 2x + 6n + 6x               ---> open parenthesis

7x - 2x + 7n + 6 -2                         ---> rearrange to bring like terms together

5x + 7n + 4                                     ---> simplify

:)

Answer:

5x + 13n + 4

Step-by-step explanation:

Since we have to combine like terms, let's start with values of n.

(7x + 7n) + (-2 - 2x) + (6n + 6) =

7n + 6n = 13n

Now we can rewrite the equation as

(7x + 13n) + (-2 - 2x) + 6

Now let's add values of x

7x + -2x = 5x

Now we can rewrite the equation as

5x + 13n + -2 + 6

Now let's add the constants

-2 + 6 = 4

There are no more like terms

Final Answer:

5x + 13n + 4

ACCESS MORE